2017
DOI: 10.6007/ijarbss/v7-i6/3007
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Sprint Ability Depending on the Level of Condition among University Soccer Players

Abstract: The purpose of this study is to investigate the repeated sprint ability (RSA) performance among university soccer players. Twenty-four university representatives were voluntarily recruited as participants of this study and were asked to perform the RSA test that was modified which includes change of direction component in it. Participants were required to perform the RSA test in two conditions, with and without ball. Sprint time, fatigue index (FI) and percentage of decrement score of sprinting (Sdec) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Findings of this study is hoped to be beneficial for the coaches in order to plan good training programs for their players. As research article is one of the sources of references for the coaches to enhance their knowledge in coaching (16)(17)(18)(19), researchers are encouraged to perform more studies on football training methods so that the sources will keep increasing in order to help the development of football performance.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study is hoped to be beneficial for the coaches in order to plan good training programs for their players. As research article is one of the sources of references for the coaches to enhance their knowledge in coaching (16)(17)(18)(19), researchers are encouraged to perform more studies on football training methods so that the sources will keep increasing in order to help the development of football performance.…”
Section: Discussionmentioning
confidence: 99%
“…As the most popular sports in the world, many studies have been conducted in soccer including in the field of psychology [10], sociology [11,12], fitness testing [13,14] and many more. To be specific in RSA study, previous recent studies had shown that there are differences of RSA performance when performed with and without ball [6,15] thus urged the important of including ball to the testing and training sessions. As we tend to proceed to the next research progress, we tried to search for RSA testing that applied comparison of different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been conducted on how to improve performance in the game. This includes researches in fitness training and testing [6][7][8][9][10], coaching development [11][12][13][14] and psychology [14,15]. Williams and Reilly [16] states that the success factor of a football team is influenced by the sociological, physical, physiological, and psychological characteristics of the athlete.…”
Section: Introductionmentioning
confidence: 99%